Analisis Break Even Point Sebagai Alat Perencanaan Penjualan dan Laba Pada UMKM Bolu Susu Lembang Pak Bhabin - Anisa, Suci; Sembiring, Etti Ernita; Surya, Rendra Trisyanto; Hutapea, Riauli Susilawaty (Indonesian Accounting Literacy Journal, 2025)
This research was conducted to plan the desired sales and profits at UMKM Bolu Susu Lembang Pak Bhabin which will not experience a decrease in profit. The research method used is descriptive quantitative research using single product Break Even Point (BEP) analysis, Multi Product Break Even Point (BEP), profit target analysis, and Margin of Safety (MoS) analysis. Based on the research results, it is known that the BEP for a single product is Bolu Susu much as 34,360 units or Rp 1.199.086.332, Pie Susu 10.131 units or Rp 22.874.530, and Kue Balok 2.476 units or Rp 86.670.451; Multi Product BEP of at least 41,910 units for the product as a whole or Rp 1.327.507.369, then Bolu Susu that must be sold is 26,023 units, Pie Susu Pie Susu 10.719 units and Kue Balok 5.168 units; to achieve the profit target of Bolu Susu 93,202 units or Rp 3.262.069.000, Pie Susu 21.077 units or Rp 463.686.136, dan Kue Balok 6.725 unit atau Rp 235.390.077; MoS is on Bolu Susu 40% or Rp 791.433.668, Pie Susu 57% or Rp 292.519.470 and Kue Balok 78% or Rp 308.654.549.